Influence of glycolic, oxidative, and mixed metabolism on growth in swine skeletal muscle - Silva H., Maria J. (Zamorano: Escuela Agrícola Panamericana, 2024)
The present work focuses on analyzing skeletal muscle metabolism in pigs, throughout different stages of growth and investigate how muscle fiber growth varies in three types of muscle with different metabolic profiles: Longissimus dorsi (glycolytic muscle), Latissimus dorsi (mixed muscle) and Masseter (oxidative muscle). The interaction between age and muscle has influence on hypertrophy muscle is also explored.The study was conducted with 25 selected castrated pig from the Kansas State University research facility. The pigs were fed according to a staggered feeding plan to meet their nutritional requirements at different stages of growth, were sampled at five slaughter time points from 20 to 180 days of age. The results revealed that there is not significant difference in Mitochondrial DNA abundance between oxidative and glycolytic muscle fibers. This contrasts with earlier research suggesting that oxidative muscle fibers tend to have a higher amount of Mitochondrial DNA. It is suggested that other factors than metabolic activity may influence this difference. In terms of the amount of Mitochondrial DNA (mtDNA), a peak was observed at 87 days of age, which could be related to the increase’s energy demands of muscle at this stage and the transition from a nursery diet to finisher diet. In addition, it was found that the interaction between age and muscle does significantly affect muscle growth. While locomotive muscle, such as Longissimus dorsi and Latissimus dorsi, showed continuous growth after 53 days, the Masseter muscle, related to chewing and located in the head, experienced significant growth after 120 days.